The Influence Of Human Development Index (Hdi), Unemployment, And Economic Growth On Crime Rates In Banjarmasin City - Ridhani, Rendy Wahyu; Yunani, Ahmad; Mahyuni , Mahyuni (Indonesian Journal of Multidisciplinary Science, 2025)
Sustainable regional development can be seen from the low crime in a place. The development of the times and the very fast dynamics of knowledge and technology in the era of society 5.0 make fierce competition in the field of human life including social, economic, ethical, morality and ideological changes. This study aims to partially and simultaneously examine the influence of the Human Development Index (HDI), unemployment and economic growth on the crime rate in Banjarmasin City. The approach of this study is a quantitative approach with the Multiple Linear Regression Analysis Method with a data period from 2004-2024. The results of this study show that partially the Human Development Index (HDI) has a positive and significant effect on the crime rate in Banjarmasin City. The unemployment variable has a positive and insignificant influence on the crime rate in Banjarmasin City, while economic growth has a negative and insignificant influence on crime in Banjarmasin City. simultaneous testing, the Human Development Index (HDI), unemployment and economic growth have a significant effect on the crime rate in Banjarmasin City.